Zakat: wealth cleanliness - Karim, Fatimah (2021)
The aim of this article was to clarify the significance of zakat as wealth and soul purification and highlight the impact of zakat to society. As one of the pillars of Islam, zakat is a form of obligatory charity that has the potential to ease the suffering of millions. With the literal meaning of the word being ‘to cleanse’, Muslims believe that paying zakat purifies, increases, and blesses the remainder of their wealth, and cleanses a Muslim's soul from being stingy, greedy, and proud. By paying zakat, Muslims are able to develop a sense of sympathy towards people in need, eliminate selfishness and clean poverty in the society. This article found that zakat signifies a major economic means for establishing social justice which led to prosperity and security and brings the sense of happiness and hope into society.